Delving into EFL Students' Difficulties in Translation: A Case Study of the English Department at Borneo Tarakan University - Saputra, Qalbi Arianto; Winarno, Winarno; Tanjung, Firima Zona (Universitas Borneo Tarakan, 2024)
The purpose of the research was to analyze translation errors and difficulties based on the implementation methods used by the students. This research applied a type of qualitative research with a case study model. The sample of the research consisted of six interviewees, consisting of three students from class Al and three others from class A2 of the sixth semester at the Department of English Education, Borneo University Tarakan. The instruments were the interview guide and documentation (students' academic reports). In the process of analyzing the translation, the researcher used the translation method based on Newmark's theory. The results showed that the students only used two methods to translate the text the word-for-word translation method and the free translation method. The research results indicated that the students who used the free translation method produced different translation results due to their creativity and understanding of similar contexts. Students also had difficulty with the use of free translation in determining the correct grammar and context for the sentence. On the contrary, the users of the word-for-word translation method have similar translation results among students who refer to the literal word translation method, most of them also have translation results that are out of the context of the sentence in terms of the literal meaning of the source language to the target language. Students also expressed difficulties with word-for-word translation, with students struggling to find the context of the sentence and the correct use of grammar for their translations.